2018
DOI: 10.1016/j.stemcr.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Screening Identifies Enhancers of Mutant Oligodendrocyte Survival and Unmasks a Distinct Pathological Phase in Pelizaeus-Merzbacher Disease

Abstract: SummaryPelizaeus-Merzbacher disease (PMD) is a fatal X-linked disorder caused by loss of myelinating oligodendrocytes and consequent hypomyelination. The underlying cellular and molecular dysfunctions are not fully defined, but therapeutic enhancement of oligodendrocyte survival could restore functional myelination in patients. Here we generated pure, scalable quantities of induced pluripotent stem cell-derived oligodendrocyte progenitor cells (OPCs) from a severe mouse model of PMD, Plp1jimpy. Temporal phenot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 52 publications
(67 reference statements)
1
33
0
Order By: Relevance
“…4c, d) were stimulated to differentiate towards an oligodendrocyte fate by addition of thyroid hormone, and MBP+ oligodendrocytes were quantified. As expected 22 , jimpy cultures contained only rare surviving MBP+ oligodendrocytes with a concomitant loss in total cells (Fig. 3a-c).…”
Section: Main Textsupporting
confidence: 84%
See 1 more Smart Citation
“…4c, d) were stimulated to differentiate towards an oligodendrocyte fate by addition of thyroid hormone, and MBP+ oligodendrocytes were quantified. As expected 22 , jimpy cultures contained only rare surviving MBP+ oligodendrocytes with a concomitant loss in total cells (Fig. 3a-c).…”
Section: Main Textsupporting
confidence: 84%
“…CR- impy iPSCs were derived and characterized for this study (line identifier jpCR100.1). Isogenic comparator jimpy (line identifier i.jp-1.6) and wild-type (line identifier i.wt-1.0) iPSC lines were described and characterized separately 22 . Genotypes of iPSCs were re-verified prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…As examples, Fu et al used PLLA fibers to investigate the unique microtubule biology in oligodendrocytes, while Weightman et al demonstrated that OPCs rely on the presence of astrocytes to survive and elongate on a 3D fibrous scaffold [ 211 , 212 ]. Others have used electrospun fibers to investigate the oligodendroglial pathobiology of CNS diseases, such as multiple sclerosis, perinatal brain injury, Pelizaeus–Merzbacher disease, and Alexander disease [ 213 , 214 , 215 , 216 ]. Additionally, these fibrous scaffolds have been used to screen for potential therapeutics that target underlying molecular mechanisms relating to myelination in CNS disease.…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Additionally, these fibrous scaffolds have been used to screen for potential therapeutics that target underlying molecular mechanisms relating to myelination in CNS disease. Using electrospun fiber model systems, various molecules have already been screened and shown to reduce OPC stress-related death, improve oligodendrocyte maturation, and reverse demyelinating processes [ 215 , 217 , 218 , 219 ]. For this reason, electrospun fibers will continue to be used as they provide a facile and reproducible myelinating assay [ 220 ].…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…It is not unlikely that the selective loss or deposition of myelin in specific brain regions, such as occurs in Hypomyelination with Brain Stem and Spinal Cord Involvement and Leg Spasticity (HBSL) (Taft et al, 2013 ; Fröhlich et al, 2018 ), is driven by a dysfunction of multiple brain cell types. For these reasons brain organoids in which these critical cooperative cell types are appropriately produced are valuable tools for studying (de)-myelination in health and disease states and constitute potential drug testing platforms for diseases that affect myelination, such as Pelizaeus-Merzbacher disease (Elitt et al, 2018 ; Nobuta et al, 2019 ) and HBLS.…”
Section: Discussionmentioning
confidence: 99%